(untitled) (Global Journal of Medical Research, 2023)
Introduction Patients with disabilities have limitations in basic daily activities and social participation so they have late-diagnosed comorbidities such as malnutrition Objective To describe the nutritional status of adults with deficiencies and disability secondary to cardiovascular diseases CVD in Motavita-Colombia from January to December 2021 Methodology A quantitative observational cross-sectional descriptive study Ten patients were included and the information was collected with a structured nutritional survey Washington questionnaire body mass index percentage of body fat and short battery of physical performance The literature search was conducted in PubMed EMBASE Web of Science UpToDate Scopus and Google Scholar as well as international guidelines resolutions theses and nutrition chapters The descriptive statistical analysis was performed with the Excel program